How Much Shallow Coral Habitat Is There on the Great Barrier Reef? - Roelfsema, Chris M.; Lyons, Mitchell B.; Castro-Sanguino, Carolina; Kovacs, Eva M.; Callaghan, David; Wettle, Magnus; Markey, Kathryn; Borrego-Acevedo, Rodney; Tudman, Paul; Roe, Meredith; Kennedy, Emma V.; Gonzalez-Rivero, Manuel; et al. (Remote sensing (Basel, Switzerland), 2021)
Australia’s Great Barrier Reef (GBR) is a globally unique and precious national resource; however, the geomorphic and benthic composition and the extent of coral habitat per reef are greatly understudied. However, this is critical to understand the spatial extent of disturbance impacts and recovery potential. This study characterizes and quantifies coral habitat based on depth, geomorphic and benthic composition maps of more than 2164 shallow offshore GBR reefs. The mapping approach combined a Sentinel-2 satellite surface reflectance image mosaic and derived depth, wave climate, reef slope and field data in a random-forest machine learning and object-based protocol. Area calculations, for the first time, incorporated the 3D characteristic of the reef surface above 20 m. Geomorphic zonation maps (0–20 m) provided a reef extent estimate of 28,261 km2 (a 31% increase to current estimates), while benthic composition maps (0–10 m) estimated that ~10,600 km2 of reef area (~57% of shallow offshore reef area) was covered by hard substrate suitable for coral growth, the first estimate of potential coral habitat based on substrate availability. Our high-resolution maps provide valuable information for future monitoring and ecological modeling studies and constitute key tools for supporting the management, conservation and restoration efforts of the GBR.